2020
DOI: 10.1080/09649069.2020.1796219
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented times: some thoughts on the consequences of the COVID-19 pandemic from a family and social welfare law perspective

Abstract: This article has been republished with minor changes. These changes do not impact the academic content of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…This condition, on the one hand, can create a quality time and intimate interactions among family members, but on the other hand, it may lead to long-standing high conflicts, occasionally domestic violence, and divorce ( Lebow, 2020b ). In this condition, a home can be described as a place of warmth, love, and safety or as a place of intimidation, abuse, and fear ( Hitchings & Maclean, 2020 ). Other studies found a positive outlook on the COVID-19 pandemic regarding the necessity of focusing on and enjoying family relationships, especially taking advantage of the pandemic's gift of extended time together ( Evans et al, 2020 ; Holmberg et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This condition, on the one hand, can create a quality time and intimate interactions among family members, but on the other hand, it may lead to long-standing high conflicts, occasionally domestic violence, and divorce ( Lebow, 2020b ). In this condition, a home can be described as a place of warmth, love, and safety or as a place of intimidation, abuse, and fear ( Hitchings & Maclean, 2020 ). Other studies found a positive outlook on the COVID-19 pandemic regarding the necessity of focusing on and enjoying family relationships, especially taking advantage of the pandemic's gift of extended time together ( Evans et al, 2020 ; Holmberg et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Als problematisch an einer rein medienvermittelten Interaktion wird zudem die Etablierung einer tragfähigen Arbeitsbeziehung [28] und der Aufbau neuer Beziehungen beschrieben, besonders bei Adressaten mit psychischen Problemen [29]. Dies hängt damit zusammen, dass Vertraulichkeit bei medienvermittelten Interakti-onen schwerer herzustellen ist, weil nicht ausgeschlossen werden kann, dass weitere Personen "mithören", von den notwendigen technischen und kompetenzbezogenen Anforderungen aufseiten der Fachkräfte und der Adressaten ganz zu schweigen [30]. Unter solchen Bedingungen steigt die Schwierigkeit, typischen sozialpädagogischen Herausforderungen angemessen zu begegnen und diese zu bewältigen.…”
Section: Diskussion -Die Corona-pandemie Als Brennglasunclassified
“…This lead to containment: quarantine, lockdowns, and curfews in turn creating conflicts, tensions, and violence manifesting upon contact with infected persons ( 1 , 15 , 16 ). Consequently, it leads to an overall breakdown of the individual, family, and society with enormous changes and unparalleled consequences-financial and medical ( 17 , 18 ). Moreover, there are economic, social, and community impacts ( 10 , 19 ) despite the assessments and investigations from the medical perspective and daily data release from the Ministry of Health.…”
Section: Introductionmentioning
confidence: 99%